Low Serum DHEAS Predicts Increased Fracture Risk in Older Men: The MrOS Sweden Study. (30th March 2017) - Ohlsson, Claes; Nethander, Maria; Kindmark, Andreas; Ljunggren, Östen; Lorentzon, Mattias; Rosengren, Björn E; Karlsson, Magnus K; Mellström, Dan; Vandenput, Liesbeth
ABSTRACT: The adrenal‐derived hormones dehydroepiandrosterone (DHEA) and its sulfate (DHEAS) are the most abundant circulating hormones and their levels decline substantially with age. DHEAS is considered an inactive precursor, which is converted into androgens and estrogens via local metabolism in peripheral target tissues. The predictive value of serum DHEAS for fracture risk is unknown. The aim of this study was, therefore, to assess the associations between baseline DHEAS levels and incident fractures in a large cohort of older men. Serum DHEAS levels were analyzed with mass spectrometry in the population‐based Osteoporotic Fractures in Men study in Sweden ( n = 2568, aged 69 to 81 years). Incident X‐ray validated fractures (all, n = 594; non‐vertebral major osteoporotic, n = 255; hip, n = 175; clinical vertebral, n = 206) were ascertained during a median follow‐up of 10.6 years. DHEAS levels were inversely associated with the risk of any fracture (hazard ratio [HR] per SD decrease = 1.14, 95% confidence interval [CI] 1.05–1.24), non‐vertebral major osteoporotic fractures (HR = 1.31, 95% CI 1.16–1.48), and hip fractures (HR = 1.18, 95% CI 1.02–1.37) but not clinical vertebral fractures (HR = 1.09, 95% CI 0.95–1.26) in Cox regression models adjusted for age, body mass index (BMI) and prevalent fractures. Further adjustment for traditional risk factors for fracture, bone mineral density (BMD), and/or physical performance variables as well as serum sex steroid levels only slightly attenuated the associations between serum DHEAS and fracture risk. Similarly, the point estimates were only marginally reduced after adjustment for FRAX estimates with BMD. The inverse association between serum DHEAS and all fractures or major osteoporotic fractures was nonlinear, with a substantial increase in fracture risk (all fractures 22%, major osteoporotic fractures 33%) for those participants with serum DHEAS levels below the median (0.60 μg/mL). In conclusion, low serum DHEAS levels are a risk marker of mainly non‐vertebral fractures in older men, of whom those with DHEAS levels below 0.60 μg/mL are at highest risk. © The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.